Quantitative Problem Solving in Natural Resources - Moore, Peter L. (Open textbook library., 2018)
This text is intended to support courses that bridge the divide between mathematics typically encountered in U.S. high school curricula and the practical problems that natural resource students might engage with in their disciplinary coursework and professional internships.